Parenting and Mental Health needs of Young, Maltreated parents: implications for Prevention of intergenerational child maltreatment - Aparicio, Elizabeth M. (Journal of family violence, 2023)
PurposeChildren of young parents are at elevated risk for child abuse and neglect due to myriad challenges. Despite the dual need for parenting support and mental health support, most literature and programs separate these and do not address maltreated parenting youths’ intergenerational context. The current study explores parenting and mental health needs as intertwined, uplifting experiences of young adult mothers with child maltreatment histories, professionals serving them, and mothers’ own caregivers.MethodThrough a community-engaged research process, this grounded theory study was co-conceptualized and conducted through a university-community-based organization partnership. We conducted in-depth interviews with 23 participants: nine young, maltreated mothers aged 18–25 (M = 20.9) years, 14 professionals and two caregivers. Data were collected in the community and analyzed using grounded theory methods. We transcribed each interview and analyzed the transcripts using a structured process of open, focus, axial, and selective/theoretical coding. Rigor was enhanced through several strategies including reflexivity and member checking.ResultsGrounded theory analysis produced a detailed model of the process of accessing and receiving mental health and parenting support among young, maltreated mothers, including (1) Reckoning with the Impact of Childhood and Adolescent Trauma on Mental Health and Parenting; (2) Reaching Out; (3) Receiving Parenting Support; (4) Receiving Mental Health Support; and (5) Seeking a Change.ConclusionsFindings support a comprehensive approach for supporting young parents in improving the trajectories of their families through integrated approaches to parenting and mental health intervention.